20+15x+20(x-1)+15(x-1)=245

Simple and best practice solution for 20+15x+20(x-1)+15(x-1)=245 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20+15x+20(x-1)+15(x-1)=245 equation:


20+15x+20(x-1)+15(x-1)=245

We simplify the equation to the form, which is simple to understand
20+15x+20(x-1)+15(x-1)=245

Reorder the terms in parentheses
20+15x+(+20x-20)+15*(x-1)=245

Remove unnecessary parentheses
+20+15x+20x-20+15+*(+x-1+)=+245

Reorder the terms in parentheses
20+15x+20x-20+(+15x-15)=245

Remove unnecessary parentheses
+20+15x+20x-20+15x-15=+245

We move all terms containing x to the left and all other terms to the right.
+15x+20x+15x=+245-20+20+15

We simplify left and right side of the equation.
+50x=+260

We divide both sides of the equation by 50 to get x.
x=5.2

See similar equations:

| -3-(-27+4)= | | 2(2x+7)=6x-8 | | 18x^2+48x+32=0 | | -4=x/2-5 | | (r^2-20tw)(4wr+5tr)= | | s^2+17s=-52 | | 9[2(3n+x)-11x]+3(x-3n)= | | e-58=43 | | p+6h=5 | | 18f=4.5*8 | | -x^2+11x-30=0 | | 4a-84=10a | | 2(-2)=-y+3 | | p/3-2=-56 | | 3x-10=23x | | (-8x)-2x=0 | | 244=-8(1+5x)-8 | | 5s-2+3(5-11)=5 | | 1.6y=6 | | (r^2-20tw)= | | -x^2+23x-132=0 | | 9x^2+11x+18=0 | | 18f=126*3 | | 5(20x-40)=48 | | 9x^2+11x+8=0 | | 8w-35=3w | | 3d=3.6*2.5 | | r^2-20tw= | | y=4.2-2.8x | | x^2+61=12x | | 9+7x=6x+19 | | 8x+6y=16 |

Equations solver categories